Implementing Drinking Water Supply System Policy in Kotamobagu City, Indonesia: Technical Operations, Monitoring, and Service Performance - Regina O. Mokoginta; Ferdinand Kerebungu; Julien Biringan (JR Education, 2026)
The study responds to the continuing gap between the public mandate to provide safe, adequate, and sustainable drinking water and the actual condition of local SPAM services, where overall service coverage remains low, distribution performance is uneven, several systems require maintenance, and institutional arrangements have not yet enabled fully focused management. Using a qualitative descriptive approach, the original article collected data through interviews, observation, and documentation involving the Head of Public Works and Spatial Planning Office, the Head of Human Settlements Division, technical sanitation staff, and community users of SPAM services. The findings show that SPAM policy has been implemented through technical operation, maintenance, monitoring, reporting, and service delivery activities; however, implementation has not yet reached optimal performance. Key problems include insufficient intake capacity, water leakage in aging distribution networks, limited maintenance funding, weak water quality surveillance due to budget constraints, unfilled UPTD institutional structure, limited certified human resources, manual complaint handling, and declining local revenue from the water service. The article argues that policy strengthening must move from fragmented operational activity toward integrated water governance that combines infrastructure renewal, institutional activation, digital monitoring, water quality assurance, responsive customer service, and sustainable financing. The study contributes to public administration literature by showing that local drinking water policy is not only a technical infrastructure problem, but also an implementation problem shaped by resources, bureaucratic structure, communication, service accountability, and community trust.